On the estimation of muscle fiber conduction velocity using a co-linear electrodes array - Meste,O; Muhammad,W; Rix,H; Farina,D (2001)
The problem of estimating the average Conduction Velocity (CV) in the muscle fibers is considered. The velocity is estimated from an array of noisy deterministic and unknown Motor Unit Action Potentials (MUAP) acquired by an array of K co-linear electrodes. In this array a vector of (K-1) independent time delays (TD) are to be estimated. For a given length of the array, the number K has to be determined in order to improve the estimation of the velocity. In this communication we show the influence of the value of K in the CV estimation in presence of noise and changes in the MUAP shape along the array.